PEMBERDAYAAN KELOMPOK PEMANDU WISATA SEBAGAI KADER TANGGAP COVID-19 DAN PELATIHAN PEMANFAATAN MEDIA SOSIAL DALAM MENDUKUNG USAHA TRAVEL - Wijaya, M.D.; Indraningrat, A.A.G.; Idawati, I.A.A. (Buletin Udayana Mengabdi; Vol 21 No 2 (2022): Buletin Udayana Mengabdi, 2022)
Tourism sector is heavily affected by the COVID-19 pandemic and there is no exception for our partners, a tour guide group that providing services for East Asia’s tourists. Their income fell drastically because international flights are closed and unnecessary travel is avoided. However, they are still eager to return to the tourism field when the pandemic is over. Therefore, counseling about the threats and modes of transmission of COVID-19 was provided, as well as training on the health protocols in running a post-pandemic tour guide service business and the use of social media for promotion. The methods used were focus group discussions, counseling and training related to COVID-19 and the application of health protocols, as well as training on the use of social media. The pretest and posttest results show that there is an increase in the partners’ knowledge regarding COVID-19 risks and its transmission, as well as the use of social media for promotion. The implementation of health protocols in tour guide services has also been carried out. It is concluded that this program has provided additional insight for tour guides in preparing themselves in facing the post-pandemic tourism, as well as being more creative in promoting their services.   Keywords: empowerment, tour guide, COVID-19, health protocols, online promotion